Stage to Change Eating behavior and physical activity among adolescents with an excess body mass: impact on metabolic profile - Bolognese, Marciele Alves (2020)
Introduction: Obesity in children and adolescents is usuallyrelated to metabolic alterations, and intervention programs are one of the strategies for the treatment of obesity and associated comorbidities. At the beginning of the intervention, the stages of readiness to change behavior indicate specific habits that the teenager plans to modify or not, and how long he or she intends to make the alterations. Objective: To assess the metabolic profile and their association with the stages of readiness to change eating habits and exercise behaviors in adolescents with overweight. Methods: Eighty-three adolescents with excess body weight underwent an assessment of anthropometric variables and metabolic profile (glucose, total cholesterol, LDL-c, HDL-c, non-HDL-c, VLDL, triglycerides, insulin). Besides, the stages of readiness to change behaviors for “size and amount of portions,” “amount of fat in the diet,” fruits and vegetable consumption,” and “physical activity practice,” anthropometric variables and metabolic profile were compared according to the stages of change. Results: About “fruits and vegetable consumption,” adolescents in the Maintenance group presented lower body weight than those from Action and Preparation groups. The Action group presented higher body weight than group “Contemplation” and it showed higher non-HDL-cholesterol than the groups “Pre-contemplation” and “Preparation.” In “physical activity practice,” the Maintenance group presented lower body weight, Body Mass Index, and body fat (in kg) than Action, Preparation, and Contemplation groups. The alterations in HDL-cholesterol reduced as the stages of change progressed in the “physical activity practice” domain. Conclusion: The stages of readiness to change behaviors impact anthropometric and metabolic variables in adolescents with excess body weight, and it is a recommended instrument to monitor intervention programs.